Hf–W chronology of the eucrite parent body. (1st May 2015) - Touboul, Mathieu; Sprung, Peter; Aciego, Sarah M.; Bourdon, Bernard; Kleine, Thorsten
Abstract: The 182 Hf– 182 W systematics of 12 whole-rock eucrites, including basaltic and cumulate samples, have been investigated. The Hf–W isotope systematics of both basaltic and cumulate eucrites are consistent with derivation from a single mantle source characterized by a strongly suprachondritic Hf/W ratio ( 180 Hf/ 184 W of ∼19). The elevated Hf/W of this mantle source was established by core formation within ∼1 Ma after CAI formation or, alternatively, represents that of the residual melt of a magma ocean from which the eucrites ultimately formed. In the latter case the time of core formation is more uncertain and core formation may have occurred slightly later than ∼1 Ma. The investigated basaltic eucrites fall into three distinct age groups with Hf–W ages of ∼4 Ma (Stannern), ∼11 Ma (Bereba, Bouvante) and ∼22 Ma (Camel Donga, Juvinas) after CAI formation and provide evidence for a protracted history of magmatism and crustal metamorphism on the eucrite parent body, lasting for at least ∼20 Ma. Evidence for even later activity is provided by the cumulate eucrites, which exhibit only small if any variations in 182 W/ 184 W in spite of variable 180 Hf/ 184 W, indicating cooling below the Hf–W closure temperature when 182 Hf was nearly extinct. On the basis of three cumulate eucrites, a Hf–W age of 38 ± 21 Ma is inferred, but even younger ages would also be consistent with the Hf–W data.